A designable magnetic MOF composite and facile coordination-based post-synthetic strategy for the enhanced removal of Hg2+ from water1. Issue 21 (7th June 2015) - Huang, Lijin; He, Man; Chen, Beibei; Hu, Bin
<x xml:space="preserve">Abstract</x> A magnetic MOF composite with a core–shell nanostructure was prepared and demonstrated to be effective for the removal of Hg2+ from water.